2021
DOI: 10.3390/sym13040712
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Key Formulations of Topology Optimization on an Example of Cantilever Bending Beam

Abstract: Topology optimization is a modern method for optimizing the material distribution in a given space, automatically searching for the ideal design of the product. The method aims to maximize the design performance of the system regarding given conditions. In engineering practice, a given space is first described using the finite element method and, subsequently, density-based method with solid isotropic material with penalty. Then, the final shape is found using a gradient-based method, such as the optimality cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…When it comes to engineering design, the topology optimization process, which relies on mathematical algorithms, greatly simplifies the task of a designer by recommending alternative design options. Considering a design space and a set of constraints (such as loads and BCs), topology optimization is an example of the computational approach that makes it possible to determine the best material distribution within that space [ 51 , 52 ]. The overall weight of the intended product can be significantly reduced while still retaining the appropriate strength and rigidity with the application of topology optimization in the design process [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…When it comes to engineering design, the topology optimization process, which relies on mathematical algorithms, greatly simplifies the task of a designer by recommending alternative design options. Considering a design space and a set of constraints (such as loads and BCs), topology optimization is an example of the computational approach that makes it possible to determine the best material distribution within that space [ 51 , 52 ]. The overall weight of the intended product can be significantly reduced while still retaining the appropriate strength and rigidity with the application of topology optimization in the design process [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…When predicting worst-case optimized designs, the elemental size dependence as well as the filtering process should be considered. Sotola et al found that solutions of a topology optimized cantilever beam differed when using different elements and filter parameters (Sotola et al, 2021). They also found that penalty factor was a key parameter in their model.…”
Section: Tablementioning
confidence: 99%
“…The presented article by [41] studies the effect of key formulations of the TO problem on the design performance, focusing on sensitivity analysis using the implementation of mathematical programming techniques in MATLAB software. Basically, the mesh independence filter works to avoid numerical instabilities, such as checkerboard, mesh dependence and local minima [42].…”
Section: Filter Schemementioning
confidence: 99%